Adhesive Characteristic and Mechanism of Ballastless Track Sealant in Hydrolysis Condition - Xue, Hengxiao; Tan, Yiqiu; Sha, Aimin (Frontiers in Materials, 2020)
The current evaluation method cannot predict accurately the hydrolysis resistance of sealants applied in ballastless slab track. And the degradation mechanism of sealant in hydrolysis condition has not been researched systemically. In this paper, the hydrolysis resistance of different sealants was researched with the aid of the self-developed direct tensile test method. The Atomic Force Microscope (AFM) was employed to analyze the micro-adhesion force on the surface of sealants, and thereby the correlation between macro-behavior and the micro-mechanism of sealants during hydrolysis was established. Results showed that the characteristics of the interface between sealants and substrates are reduced after hydrolysis, and that sealants with higher soft-segment content have good resistance to hydrolysis. Reduction of the bonding area after hydrolysis is also an important factor in the reduction of the characteristics of the adhesive interface. The micro-adhesion force of soft segments shows a fluctuating reduction tendency, and that of hard segments reduces more significantly during hydrolysis. The micro-adhesion force has good correlation with the maximum tensile force, but a poor correlation with failure displacement. The maximum tensile force is proved to be an optimal evaluation index in determining the hydrolysis resistance of sealants.